Diversification of Lontar Fruit and Community Empowerment by Thematic KKN Students in Awangpone District - Annisa Zakiyah Darojat; Ade Muspa; Indah Ayu Risnah; Riskawati Riskawati; Nur Eva Sapartina; Rahmawati Rahmawati; Karmilasari Karmilasari; Andi Nurlianih (Universitas Muhammadiyah Sidenreng Rappang, 2026)
The Thematic KKN of Sipatokkong Mambo University is a student community service program. This activity took place in Awangpone District, spanning Jaling, Cumpiga, Abbanuang, and Carebbu Village, from September 15 to October 17, 2025, under the theme of diversification of lontar fruit (Borassus flabellifer). This Thematic KKN aimed to provide community living experiences for students and introduce innovations in diversifying lontar fruit into nata de lontar and lontar jam. The method of this activity consisted of observation, formulation of main and additional programs, implementation of work programs, monitoring, and evaluation. The results are the implementation of the main program in the form of training in making nata de lontar and lontar jam, logo design, and digital marketing. The additional program is community programs in health, hygiene, and social matters. The products produced from this Thematic KKN are nata de lontar and lontar jam.